(untitled) (Research, Society and Development, 2025)
Osteopetrosis is a rare, hereditary osteopathy that leads to an abnormality in bone density due to erratic osteoclastic resorption, which can also compromise neurological and hematological functions and even lead to growth retardation. It is usually diagnosed in the first decade of life, and bone fractures tend to be present at its initial manifestation. Objective: To report the evolution of a 3-month-old patient with thrombocytopenia, hypotonia, seizures, and malnutrition, initially to be clarified, until the diagnosis of osteopetrosis and clinical outcome. Methods: Data will be obtained from electronic and paper medical records. The study was approved by the Research Ethics Committee at the hospital of origin and did not require the Informed Consent Form (ICF), given that the patient was socially vulnerable and had been placed under state guardianship. This is an observational, descriptive study, without a control group, in the form of a clinical case report. Results/Conclusion: Its scientific relevance lies in the importance of reporting a rare case whose early diagnosis directly affects its prognosis, since definitive treatment includes bone marrow transplantation.